2009
DOI: 10.1128/iai.00093-09
|View full text |Cite
|
Sign up to set email alerts
|

Glucose and Glycolysis Are Required for the Successful Infection of Macrophages and Mice by Salmonella enterica Serovar Typhimurium

Abstract: Salmonella is a widespread zoonotic enteropathogen that causes gastroenteritis and fatal typhoidal disease in mammals. During systemic infection of mice, Salmonella enterica serovar Typhimurium resides and replicates in macrophages within the "Salmonella-containing vacuole" (SCV). It is surprising that the substrates and metabolic pathways necessary for growth of S. Typhimurium within the SCV of macrophages have not been identified yet. To determine whether S. Typhimurium utilized sugars within the SCV, we con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
160
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(178 citation statements)
references
References 63 publications
18
160
0
Order By: Relevance
“…We have analysed the ability of a number of metabolic mutants in AIEC to replicate in macrophages and we have shown that glycolysis has a significant role during growth in the acidified phagosomal niche. This is similar to what has recently been reported for S. enterica serovar Typhimurium where the same mutation (DpfkAB) prevented intracellular replication of S. Typhimurium in murine RAW264.7 macrophages (Bowden et al, 2009). The DpfkAB mutant in Salmonella was also attenuated in virulence and this mutant showed significantly less colonization of BALB/c mice after either intravenous or intraperitoneal injection (Bowden et al, 2009;Paterson et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…We have analysed the ability of a number of metabolic mutants in AIEC to replicate in macrophages and we have shown that glycolysis has a significant role during growth in the acidified phagosomal niche. This is similar to what has recently been reported for S. enterica serovar Typhimurium where the same mutation (DpfkAB) prevented intracellular replication of S. Typhimurium in murine RAW264.7 macrophages (Bowden et al, 2009). The DpfkAB mutant in Salmonella was also attenuated in virulence and this mutant showed significantly less colonization of BALB/c mice after either intravenous or intraperitoneal injection (Bowden et al, 2009;Paterson et al, 2009).…”
Section: Discussionsupporting
confidence: 75%
“…This is similar to what has recently been reported for S. enterica serovar Typhimurium where the same mutation (DpfkAB) prevented intracellular replication of S. Typhimurium in murine RAW264.7 macrophages (Bowden et al, 2009). The DpfkAB mutant in Salmonella was also attenuated in virulence and this mutant showed significantly less colonization of BALB/c mice after either intravenous or intraperitoneal injection (Bowden et al, 2009;Paterson et al, 2009). Glycolysis has also been shown to be required for the replication of Shigella within the cytoplasm of infected epithelial cells (Waligora et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…First, it has been reported that inactivation of the general PTS components EI and HPr prevents the replication of this bacterium in macrophages (130). Second, deletion of EIIA Ntr was found to indirectly affect the virulence of this pathogen.…”
Section: Fig 5 Pts-catalyzed Glucose Uptake and The Eiiamentioning
confidence: 99%
“…This may slow down the growth but does not affect survival and therefore leave little scope for the development of resistance. Metabolism associated genes of pathogens have been consistently linked with virulence of major pathogens, [1][2][3][4][5][6][7][8][9] such as, role of carbon metabolism related pathways like glycolysis 10 and TCA cycle 11 in virulence of Salmonella Typhimurium and requirement of metabolism associated pathways for protection of Mycobacterium tuberculosis from host immune system. 9 Salmonella is even known to modulate host to exploit the limited supply of nutrients.…”
Section: Potential Of Peptide Transporters In Antimicrobial Therapymentioning
confidence: 99%